Economic feasibility of alternative crops in Northeast Iowa to sustain family incomes - Quandahl, Kendal (Kansas State University, 2017)
The purpose of this thesis is to identify which alternative crops could be enhance the income of Quandahl Farms the most by moving the smallest acreage from the farm’s traditional corn and soybean enterprises into its production. The considered crops are grapes, raspberries, and black currants. The objectives of this study included assessing the technical feasibility of producing the selected crops in Northeast Iowa given the agronomic conditions in the region and the agronomic requirements of the crops. The other was the assessment of the economic feasibility of the selected crops and determining the minimum acres required for each to enhance the farm’s financial situation and still allow for corn and soybeans to be the main crops. The analyses were conducted using secondary data on the selected crops from published budgets and government and extension reports as well as the historical financials of Quandahl Farms. The analyses were conducted over a 10-year horizon to ensure a significant duration of cash flow and allow the establishment of the alternative crops. In that 10-year period, the net present value of Quandahl Farms income is $214 per acre per year. Additionally, the analyses were evaluated under four alternative scenarios of prices and yield for each of the crops in addition to the base scenario. The results shows that grapes and black currants were not economically feasible in Northeast Iowa even though they were agronomically feasible. On the contrary, raspberries were found to be both technically and economically feasible in Northeast Iowa. The net present value under that base scenario for raspberries was $23,267 at a discount rate of 4.5%. Based on the net present value of corn and soybean revenue of the same period, it is estimated that taking 22 acres from the current production and putting it into raspberries would increase average farm income by $60,000. The study shows there is an opportunity to allocate a relatively small proportion of current corn and soybean acreage to raspberries to significantly increase farm incomes. As a result, it is recommended to the principals of Quandahl Farms to consider making this small investment in raspberries to protect the farm from the frequent vicissitudes of farm incomes. The next step after their agreement is to develop the business plan to implement such an investment.
Keywords: Agronomic Feasibility; Economic Feasibility; Alternative Crops; Farm Income; Financial Analysis; Raspberries